Analysis Of Sus Expenses With The Hospitalization Of Patients Affected By Headaches In The State Of Ceará, Between 2013 And 2022 - Lopes, Thiago Luís Marques; Sousa, Arthur Vitor Couto De; Ferreira, Eduarda Lima Verde; Filho, Hildel Freire Leite; Clarindo, José Fernando Muniz (Headache Medicine, 2023)
Full abstract in PDF.